HERBAGE PRODUCTION AND NUTRITIVE VALUE OF ALPINE PASTURES IN UPPER KAGHAN VALLEY, KHYBER PAKHTUNKHAWA, PAKISTAN - M. Mobashar; G. Habib; M. I. Anjum; I. Gul; N. Ahmad; A. Moses; A. Mahmood (Journal of Animal and Plant Sciences, 2017)
Grasses, forbs and shrubs of alpine pastures harvested at three different intervals from four different altitudinal zones (2925-4184 m), Basel, Jalkhad, Gittidas and Burawai in upper Kaghan valley, Pakistan, were assessed for herbage production and nutritive value. Sample collection was accomplished by cutting above ground biomass at a 0.5m height. The results showed that herbage production was significantly (P<0.001) higher (333 kg/ha) for grasses and shrubs (192 kg/ha) in Burawai than Basel and Gittidas. The total herbage production was maximum in Burawai (1003 kg/ha) and was minimum in Basel and Gittidas. Herbage production of grasses and forbs was higher at 2nd harvest and was also significantly (P<0.01) affected by location x herb and harvest x herb interactions. The crude protein (CP) was higher in shrubs (14.8%) and forbs (13.6%) as compared to grasses (12.3%). The CP was the highest in herbages in Basel at 1st harvest. In vitro dry matter digestibility (IVDMD) of herbage was significantly higher (P<0.001) at Basel and Burawai followed by Gittidas and Jalkhad showing higher value for shrubs (67.1%) than forbs (56.2%) and grasses (54.2%) which was significantly affected (P<0.01) by location x herb interactions. Shrubs had more DM than grasses and forbs. Forbs showed higher ash contents at 1st harvest and lower at 3rd harvest as compared to grasses and shrubs. Grasses had greater NDF, ADF and hemicellulose contents than forbs and shrubs. Results demonstrated that variations in herbage production, CP and IVDMD and cell wall fractions of herbage were attributed to plant composition of the sward and harvest stage of the herbages.
Keywords: Alpine pastures; herbage production; in vitro dry matter digestibility; Kaghan Valley; Nutritive value